Evaluating the Thermal and Electrical Performance of Several Uncovered PVT Collectors with a Field Test. (June 2016) - de Keizer, Corry; de Jong, Minne; Mendes, Tiago; Katiyar, Munish; Folkerts, Wiep; Rindt, Camilo; Zondag, Herbert
Abstract: Recently, there has been a lot of interest in PV thermal systems, which generate both heat and power. Within the WenSDak project, several companies and research institutes work together to (further) develop several uncovered PVT collectors. The outdoor performance of prototypes of these collectors is being evaluated in an outdoor test setup. The three types of uncovered PVT collectors in this paper can be distinguished as an un-insulated add-on PVT collector, a PVT collector with insulation at the back and a building integrated PVT collector. In this paper, we will describe the experimental outdoor field test facility used for measuring the electrical and thermal performance. Furthermore, the results of the steady state analysis and typical collector curves are presented. In the next phase of the project, results of this field test will be used for dynamic simulations of the annual electrical and thermal energy yields for typical system designs and heat loads in the Netherlands.